Design for manufacturing : a structured approach / Corrado Poli. - Poli, Corrado, 1935- (Butterworth-Heinemann, 2001)
Design for Manufacturing assists anyone not familiar with various manufacturing processes in better visualising and understanding the relationship between part design and the ease or difficulty of producing the part.